2017
DOI: 10.4236/health.2017.94042
|View full text |Cite
|
Sign up to set email alerts
|

The Survey of Self-Regulation Behaviors and Related Factors in Elderly with Hypertension in South-East of Iran

Abstract: Hypertension is one of the most important risk factors for heart diseases today. The effect of hypertension in the elderly is higher than other age groups and it may lead to changes in their quality of life. By the increase of age, the amount of self-care behaviors of patients with hypertension decreased. Therefore, control and self-care behaviors are so important. This study has been conducted to study self-regulation behaviors and Associated Factors in elderly patients with hypertension. This study was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…Current failures in the healthcare system sub-category indicate a defect in the correct education of older people by the physician or nurses or a complex patient admission system for the visit (a telephone patient admission system) and a lot of time spent for an appointment in government clinics. The problem of incorrect education of older people by the physician or nurses was one of the specific findings of the present study, which was similar to the results of other Iranian studies (Fuladvandi et al, 2017;Nouhi and Abbaszadeh, 2016) but was not mentioned in any foreign study. The results of one study showed that the mean of drug training was 18.45 percent and dietary training was 45.14 percent (Chang, 2015).…”
Section: Concluding Discussionsupporting
confidence: 91%
“…Current failures in the healthcare system sub-category indicate a defect in the correct education of older people by the physician or nurses or a complex patient admission system for the visit (a telephone patient admission system) and a lot of time spent for an appointment in government clinics. The problem of incorrect education of older people by the physician or nurses was one of the specific findings of the present study, which was similar to the results of other Iranian studies (Fuladvandi et al, 2017;Nouhi and Abbaszadeh, 2016) but was not mentioned in any foreign study. The results of one study showed that the mean of drug training was 18.45 percent and dietary training was 45.14 percent (Chang, 2015).…”
Section: Concluding Discussionsupporting
confidence: 91%
“…This is similar to the results obtained from elderly population reported from elsewhere (Fuladvandi et al, 2017), where married people were found to have higher levels of self-regulation when compared to the unmarried population. Age group is not found to be a significant discriminator between IT professionals in their self-regulated behaviour.…”
Section: Resultssupporting
confidence: 82%
“…However, in patients with hypertension, it is found that the ability to perform self-care is still low (5)(6)(7) . This low self-regulatory ability is a factor that can lead to low self-care (8) . Studies show that self-regulation affects self-care abilities (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Low self-regulation will fail to make changes in behavior (11) . In patients with hypertension, self-regulation is low (8) . This results in the sufferer experiencing failure to make behavior changes (12) .…”
Section: Introductionmentioning
confidence: 99%